TMED9 drives non-small-cell lung cancer progression via promotion of autophagy by recruiting USP5 to deubiquitinate ATG9A - Na Liu; Guohu Han; Fusheng Zhang; Qianhui Gu; Yuanyuan Liu; Jing Jia; Xiaoren Zhu; Minbin Chen (Proceedings of the National Academy of Sciences, 2026)
Non-small-cell lung cancer (NSCLC), the predominant type of lung cancer, is characterized by high invasiveness and significant mortality. Despite its clinical impact, the molecular mechanisms driving its pathogenesis and progression remain poorly understood. This study demonstrates that TMED9 is overexpressed in NSCLC and showed using multiple independent sample sets that its expression level is significantly associated with poor patient prognosis. Gain- and loss-of-function experiments revealed that TMED9 promotes proliferation, invasion, and migration of NSCLC cells in vitro and significantly accelerates tumor growth and metastasis in vivo. Mechanistically, TMED9 interacts with ATG9A and recruits USP5 to facilitate the deubiquitination and stabilization of ATG9A, thereby activating autophagy and driving malignant progression. Notably, genetic depletion of TMED9 enhances the sensitivity of NSCLC cells to osimertinib. Collectively, these findings identify the TMED9–USP5–ATG9A signaling axis as a critical driver of NSCLC malignancy, highlighting TMED9 as a promising therapeutic target.